Restoration of normal sinus rhythm in atrial fibrillation: impact of reverse remodelling of right chambers on tricuspid regurgitation severity. (25th November 2020) - Soulat-Dufour, L; Benhamou-Tarallo, I; Lang, S; Ederhy, S; Ancedy, Y; Adavane-Scheuble, S; Chauvet-Droit, M; Nhan, P; Jean, M; Ben Said, R; Scheuble, A; Boccara, F; et al.
Abstract: Background: The severity of tricuspid regurgitation (TR) in patients with restored normal sinus rhythm (SR) after atrial fibrillation (AF) has been poorly assessed. Purpose: Our study aimed to assess (1) right chamber remodelling and (2) TR severity in patients with AF who have had their rhythms restored to normal sinus. Methods: We prospectively evaluated 94 consecutive patients hospitalized for AF who received either ablation, direct current cardioversion, or pharmacological therapy. Patients were divided into two groups according to their cardiac rhythm at 6 months follow up (6M): restoration to SR (SR group, n=54), persistence of AF (AF group, n=40). TR vena contracta (VC), TR grade severity was divided into 4 grades using an integrated approach (0: none or trace; 1: mild; 2: moderate; 3: severe TR). Two dimensional (2D) end diastolic (ED) tricuspid annulus (TA) diameter in the apical 4 chambers view, three-dimensional (3D) indexed volumes (3D Vi) of the right atrium (RA) and right ventricle (RV) in end systole (ES) and ED were acquired using transthoracic echocardiography at admission and at 6M. Results: At 6M, in the SR group a significant improvement in TR VC (Figure A) and TR grade (Figure B) were noted, whereas there was no differences in the AF group (0.41 vs. 0.42cm, p=0.24 for TR VC; 1.70 vs. 1.76, p=0.16 for mean TR grade). In the SR group a significant reduction in 3D ES RV Vi, 2D ED TA diameter, 3D ES and ED Vi of the RA (Table) were observed. Regression of TR VC was correlated with regression of right cavities parameters (ρ=0.47, p<0.001 for 2D ED TA diameter; ρ=0.34, p<0.005 for 3D ES RA Vi; ρ=0.33, p<0.005 for 3D ED RV Vi; ρ=0.29, p<0.005 for 3D ES RV Vi). Conclusion: Restoration of normal SR in patients with AF results in beneficial remodelling of right cavities at 6M of follow-up which were associated with a significant decrease in TR severity. Strategies for normal SR restoration in patients with AF and TR should be vigorously attempted. Funding Acknowledgement: Type of funding source: None